Ovariectomy Stimulates Hepatic Fat and Cholesterol Accumulation in High-fat Diet-fed Rats - Ngo Sock, E. T.; Côté, I.; Mentor, J. S.; Prud’homme, D.; Bergeron, R.; Lavoie, J.-M. (Hormone and Metabolic Research, 2013)
This study was designed to determine how estrogens withdrawal during a high-fat (HF) diet regimen affects liver triacylglycerol (TAG) and cholesterol accumulation. Female Sprague-Dawley rats were submitted to a HF (42% energy as fat) or a standard (SD) diet for 6 weeks before being either ovariectomized (Ovx) or sham operated (Sham). Thereafter, Ovx and Sham rats were kept on the same diet for another 6 weeks leading to euthanasia. Liver TAG content was increased (p<0.01) in Ovx rats but not by the HF diet alone. However, the combination of HF diet and Ovx resulted in a greater liver TAG accumulation (p<0.06) than that observed in Ovx-SD/SD. Measurement of molecular markers of liver lipid metabolism revealed an increase in transcripts of markers of lipid oxidation (CPT-1 and PGC1; p<0.05) in rats fed the HF diet. This increase was, however, substantially less if HF fed rats were Ovx. Liver total cholesterol levels were increased (p<0.01) only in the Ovx-HF/HF rats while plasma cholesterol levels were increased in Ovx-SD/SD and in SHAM-HF/HF and Ovx-HF/HF rats. Transcripts of molecular markers of cholesterol metabolism suggest that biliary acids synthesis (CYP7a-1) was reduced in Ovx-SD/SD and Sham-HF/HF rats and even more so in Ovx-HF/HF rats. It is concluded that the effects of a HF diet on liver TAG accumulation are especially observed in Ovx rats possibly through a reduction in hepatic lipid oxidation. The combination of Ovx and HF diet also acts synergistically to favor liver cholesterol accumulation.
Keywords: Lipogenesis; lipid oxidation; bile acids synthesis; cholesterol synthesis